Hubungan Antara Faktor Kesejahteraan Profesi dan Persepsi Jurnalis Harian Pagi Radar Bogor - Samiyah Samiyah; David Rizar Nugroho; Dwi Rini Sovia (UNIVERSITAS PAKUAN, 2019)
ABSTRACT This study aimed to identify the characteristic of morning-daily journalist of Radar Bogor news, the factor of morning-daily profession welfare, the perception of morning-daily journalist of Radar Bogor news and the relation between factor of profession welfare with the perception of morning-daily journalist of Radar Bogor news. The used method of this study was quantitative descriptive correlational. The used theory is Rakhmat perception theory. This study was done by spreading the questionnaire to 26 morning-daily journalists of Radar Bogor news. The used sampling technic was non-probability sampling. The analyzing data technic were statistical descriptive and statistical inferential analysis. The used counting methods of this study used the testing correlation with the formulas Ordinal Rank Spearman and Pearson Chi Square for the nominal data, for processing the data were by using SPSS 22.0 and validity testing by using the formulas of Pearson Product Moment. Validity and reliability testing stated that valid and reliable. The result of relational testing between variable was known that the relation (X1) as characteristic of morning-daily journalist of Radar Bogor news and variable (Y) as the perception of morning-daily journalist of Radar Bogor news stated that really unrelated. Then the result of relation testing between variable (X2) as factor of profession welfare with the perception of morning-daily journalist of Radar Bogor news with the variable (Y) as the perception of morning-daily journalist of Radar Bogor news stated that really unrelated. As for the result of this study related to the perception of morning-daily journalist of Radar Bogor news against profession welfare obtained data that morning-daily journalist of Radar Bogor news gave the positive perception against the factor of profession welfare.Key words: journalist, perception, the factor of profession welfare